GAMBARAN PENYAKIT PERIODONTAL PADA PASIEN DIABETES MELLITUS YANG BERKUNJUNG KE KLINIK GIGI RUMAH SAKIT UMUM DAERAH KARANGASEM TAHUN 2OI3 - Ni Nengah Suti; Ni Ketut Ratmini; I Nyoman Wirata (Jurnal Kesehatan Gigi (Dental Health Journal), 2014)
Diabetes mellitusis closely related to abnormalities in the periodontal tissues. Patient with Diabetes Mellitus (DM) that is uncontrolled with bad oral hygieneand glucose or sugar level sare high is a good medium for bacterial growth in the mouth so it will be found the presence of gingival lnflammation from gingivitis to periodontitis and acute marginal teeth shake.This study aims to describe the Periodontal Disease in Diabetes Mellitus Patients who visited the Dental Clinic General Hospital of Karangasem Regency in 2013" This study is a descriptive crossectional design. Thr population of this study all patlents with diabetes mellitus who visit the Dental Clinic General Hospital of Karangasem regency totaled 43 people.  Data collected by direct examination of the respondents with a CPITN.The results showed the number of respondents who experienced more periodontal disorders on Gendermen than with women. Periodontal disorders most common in the age group 53-62 years and at leastin the age group 33-42 years. The most frequent sextant periodontal disorders sextant VI is the mostr are and periodontal disorders are sextant II.It is recommended that provide care to patients with Diabetes Mellitus who have perlodontal disease and provide direct counseling on oral health maintenance. Further care and oral health educationis emphasizedin the age group 53-62 years